2004
DOI: 10.1128/ec.3.4.1062-1065.2004
|View full text |Cite
|
Sign up to set email alerts
|

The Two-Component Signal Transduction Protein Chk1p Regulates Quorum Sensing in Candida albicans

Abstract: Regulation of hyphal morphogenesis in Candida albicans can occur through quorum sensing (QS). A QS signal, farnesol, is produced during high-density growth and inhibits morphogenesis. However, the signal transduction pathway that regulates QS is unknown. Here, we show that a C. albicans mutant lacking Chk1p but not either the Sln1p or the Nik1p histidine kinase is refractory to the inhibitory effect of farnesol both in cell suspension and during the formation of a biofilm. This study is the first to demonstrat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
88
0

Year Published

2005
2005
2015
2015

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 129 publications
(95 citation statements)
references
References 22 publications
7
88
0
Order By: Relevance
“…How farnesol is sensed and how the signal is transmitted to this MAPK pathway remains to be determined. Interestingly, C. albicans mutants lacking the histidine kinase Chk1 (see below) are refractory to the inhibitory effect of farnesol both in cell suspension and during the formation of a biofilm (158). This indicates a role of two-component signal transduction proteins in quorum sensing and as upstream components of the Cek1 MAPK pathway.…”
Section: Signal Transduction Quorum Sensing and The Mapk Cascade Momentioning
confidence: 99%
“…How farnesol is sensed and how the signal is transmitted to this MAPK pathway remains to be determined. Interestingly, C. albicans mutants lacking the histidine kinase Chk1 (see below) are refractory to the inhibitory effect of farnesol both in cell suspension and during the formation of a biofilm (158). This indicates a role of two-component signal transduction proteins in quorum sensing and as upstream components of the Cek1 MAPK pathway.…”
Section: Signal Transduction Quorum Sensing and The Mapk Cascade Momentioning
confidence: 99%
“…The addition of farnesol blocks hyphal formation by WT cells but not chk1 null mutants (7). However, farnesol could still repress SOK1 expression in a chk1 mutant, like in WT cells or the stp3 mutant (Fig.…”
Section: Sok1 Expression Is Activated On Release From Farnesol Inhibimentioning
confidence: 99%
“…The synthesis of biologically active fluorescent analogs of farnesol was used to show that farnesol derivatives localize to the cytoplasmic and nuclear membranes (84). Kruppa et al (40) found that C. albicans mutants defective in the Chk1 histidine kinase, which has similarity to Schizosaccharomyces pombe Mak2p and Mak3p oxidative stress response proteins, are resistant to farnesol suppression of filamentation and biofilm formation. Sato et al (79) showed that the mitogen-activated protein (MAP) kinase cascade that governs filamentation under nutrient-limiting conditions is repressed upon addition of farnesol.…”
Section: Albicans and Autoregulationmentioning
confidence: 99%